Transient experimentation and modeling of a multi-microchannel evaporator - Richey, Joshua Johnhenry, author; Bandhauer, Todd, advisor; Young, Peter, committee member; Simske, Steve, committee member (Colorado State University. Libraries, 2020)
Laser diodes are semiconductor devices that convert electrical energy into light. Often, diodes are arrayed closely together to produce high optical output. Commercially available diode arrays show electro-optical efficiencies of ~50%, resulting in high heat fluxes from these compact devices. Active thermal management is warranted to prevent decreases in performance or damage to the device. Two-phase cooling in microchannels has shown great promise in steady-state studies, dissipating heat fluxes over 1.1 kW cm-2. The very high latent heat and buoyancy-driven effects associated with two-phase cooling produce large heat transfer coefficients, minimizing undesirable temperature gradients across the diode. Previous research has primarily focused on steady-state operation. Although promising steady-state results were documented, little is known on the effects of transient heat loads on microchannel flow boiling. Laser diodes can rapidly change their optical output, inducing extreme transient heat loads. Furthermore, cold start up, where the diode is stepped up directly to maximum optical output, produce transient heat loads which are especially concerning. These transient challenges need to be fully understood to usefully implement two-phase cooling of laser diode arrays. The current study investigates the effects of transient heat loads on a multi-microchannel evaporator. A silicon multi-microchannel heat exchanger with small hydraulic diameters (52 µm) and a surrogate laser diode heater, developed by Lawrence Livermore National Laboratory, is integrated into a two-phase pumped loop to perform transient experiments with pulsed and ramped heat loads. When exposed to pulsed loads, infrared temperature measurements and flow visualization showed extreme superheat temperatures (~50°C) before the onset of boiling. After the onset of boiling, unexpected flow instabilities were seen, followed by a delay in steady-state two-phase boiling that could not be explained by thermal mass of the test section. Transients in the flow conditions were also documented, and ramping heat loads showed promise in mitigating the peak temperature and flow instabilities. Furthermore, a transient thermal suite (ATTMO) developed by P C Krause and Associates (PCKA), is utilized to model the microchannel evaporator. The thermal suite is augmented to model the dynamics seen under a pulsed heat load. A reduced-order, non-computationally demanding method using a logistic function to describe the transient heat transfer coefficient is implemented into ATTMO. The transient modeling results showed a good correlation (average error of (±2.04°C) with the experimental data collected. A direct relationship between onset of boiling temperature and growth rate is shown. The results from this study show potentially dangerous peak temperatures for laser diodes. Mitigation strategies should be investigated and implemented to avoid the extreme superheat temperatures. The non-computationally demanding model developed in this research can be used in future studies to rapidly investigate the effects of heat loads and different operational parameters.